Perbedaan Padat Tebar Terhadap Performa Ikan Nila (Oreochromis niloticus) Pada Keramba Jaring Apung Di Sungai Mempawah - Sarmila, Sarmila; Warastuti, Sri; Mudlofar, Farid; Putri, Hylda Khairah; Susilawati, Susilawati; Setiawan, Agus (Jurnal Kelautan, Lingkungan, dan Perikanan, 2024)
Tilapia cultivation using floating net cages is widely carried out by the Mempawah community. However, one of the problems often experienced by tilapia fish farmers in KJA is the low survival rate and growth rate, which will impact the success of cultivation. The alternative solution offered is to conduct research to determine stocking density. Determination of stocking density is essential so that space utilization becomes more. Therefore, this study aims to obtain the optimal stocking density that provides tilapia fish’s best growth rate and survival rate. This study used a completely randomized design (CRD) with four treatments and three replications, namely (A) stocking density of 30 fish/m3, (B) stocking density of 50 fish/m3, (C) stocking density of 70 fish/m3, and (D) stocking density of 90 fish/m3. The variables collected were survival rate, growth rate, and feed conversion. The analysis results showed that the stocking density of 50 fish/m3 can provide the best growth rate, feed conversion ratio, and survival rate.